Decolonizing: the curriculum, the museum and the mind - Abdulla, Danah; Cisneros, Teresa; Francke, Andrea; Jablonskienė, Lolita ca. 20./21.Jh; Mazūraitė-Novickiené, Ieva; Mbembe, Achille 1957-; Usmanova, Alʹmira Rifovna 1967-; Pleikienė, Ieva 1971-; Smith, Marquard; Gamaker, Michelle Williams 1979- (Research as praxis, 2020)
"Decolonizing: The Curriculum, the Museum, and the Mind" tries to identify where we're at and where we might be going vis-à-vis the idea of decolonizing - better, the process of decolonization - in higher education, museums and galleries, and the ongoing legacies of colonization that shape structures and infrastructures, policies and protocols, mentalities and behaviours, and minds and bodies.